The use of the rubric as a tool of assessment and feedback of expression in French - Chao Chao, Kuok-Wa (2019)
This paper was conducted at the University of Costa Rica in 2016. The research problem was “How does the rubric for written production help teachers provide effective feedback to their students?” Existing theory emphasizes that feedback is an essential tool to help students improve their skills. Additionally, it allows them to extend their learning and become aware of their own learning process. In regard to the methodology for this research, a qualitative collaborative method was used. Three professors and their students participated in this study. A pretest was conducted before the implementation of the descriptive analytical rubric in order to document the existing assessment practices among professors. It also took place before the completion of a training workshop. A post-test was conducted after completing the investigation in December 2016. In this manner, six interviews were completed by professors teaching written expression courses as six discussion group were held with the participant students. Three interviews were conducted before the training workshop and the other three at the end of the research. Likewise, for the discussion groups, three interviews were conducted before the workshop and three at the end of the study. The results show that this assessment tool allowed instructors to evaluate and to offer effective feedback to the participants. Concerning the students, they expressed a positive attitude towards the instrument for self-evaluation of their written productions. Nevertheless, it is necessary to have some models as examples of assignments for each criterion. Taking these results into account, it is possible to conclude that the rubric is an effective tool to give feedback and to evaluate written productions